Does the Addenbrooke's Cognitive Examination‐revised add to the Mini‐Mental State Examination in established Alzheimer disease? Results from a national dementia research register. (4th May 2012) - Law, Emma; Connelly, Peter J.; Randall, Emma; McNeill, Catriona; Fox, Helen C.; Parra, Mario A.; Hudson, Justine; Whyte, Leigh‐Ann; Johnstone, Jane; Gray, Sarah; Starr, John M.
<x xml:space="preserve">Abstract</x> Objective To evaluate how much the Addenbrooke's Cognitive Examination‐revised (ACE‐R) improves the estimate of cognitive ability from the Mini‐Mental State Examination (MMSE) in people with Alzheimer disease (AD). Methods We examined itemized data in people with AD who were on the Scottish Dementia Research Interest Register drawn from eight centres across Scotland, covering 75% of the Scottish population. ACE‐R items that comprise the MMSE and those that did not (non‐MMSE items) were summed separately. We residualized MMSE total on non‐MMSE total and vice versa to derive a measure of the variance unique to each. Results Five hundred and one (258 male, 243 female) participants, mean age 75.7 (range 52–94) years were on the register, of whom 329 (160 men, 169 women) had AD. Of those with AD, 309 had a mean MMSE of 20.5 and mean ACE‐R of 57.5 measured with Pearson r = 0.92 between MMSE and ACE‐R totals, and the regression equation ACE‐R score = 3.0 × MMSE − 4.1. The unique non‐MMSE items score correlated with ACE‐R total r = 0.40 (16% of ACE‐R variance). Conclusions The ACE‐R and MMSE total scores are highly correlated. In this clinical sample of people with established AD, for an MMSE score of 24, the predicted ACE‐R score was 67.9 with 95% confidence intervals of 61.6–75.4. The extra non‐MMSE ACE‐R items improve estimates of cognitive ability by 16%. Copyright © 2012 John Wiley & Sons, Ltd.